Penggunaan Audio Visual Wordwall dalam Peningkatan Motivasi Belajar Siswa di Sanggar Bimbingan Permai Kulim Malaysia - Rifka Dian Irmayanti; Kurniawati Mutmainah; Yogi Ageng Sri Legowo; Pitaloka Dharma Ayu (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
This research has objective to examine the use of audiovisual media, specifically the term platform wall, to motivate students at Permai Guidance Studio, Kulim, Malaysia. The method used was a participatory approach where both teachers and students are actively involved in the learning process. actively in the learning process. The activity started with socialisation on the importance of using audiovisual learning aids, followed by with training for teachers to use WordWall in their classrooms. The results of this study show that using interactive learning through wordwall increases students' participation and enthusiasm compared with traditional learning methods. These findings suggest that the integration of technology into education has a positive effect on student motivation, reducing boredom and enhances the learning process.